Holistic Paradigm Contradiction of the Ultimate Principle of Remedium Against the Principle of Legality in Environmental Criminal Law Enforcement - Mashuril Anwar (Fakultas Hukum Universitas Lampung, 2020)
The advancement of marine tourism has a positive impact on local communities and also raises concerns about negative effects on coral reefs. Damage to coral reefs in Indonesia currently reaches 46 percent. The damage turns coral reefs white and threatens biodiversity and the function of coral reef ecosystems. One of the causes of damage is the oxybenzone and octinoxate content in sunscreens used by marine tourists. Hawaii has issued a law banning sunscreen lotions containing these substances. The purpose of this study was to analyze the urgency of banning sunscreens in marine tourism areas in Indonesia as a basis for drafting regulations to protect coral reef ecosystems. This study uses a jurisdictional normative approach and analyzes secondary data such as legal theory, laws and regulations, and is supported by several studies on coral reefs. The results of this study indicate that sunscreen can protect the skin from exposure to ultraviolet rays which can cause acute and chronic health problems. However, the use of oxybenzone and octinoxate as chemical filters also has the potential to cause health problems. These substances also cause coral bleaching even at the lowest settlement level. The use of sunscreen is regulated in several parts of the world. Referring to the progressive legal theory, the prohibition of using sunscreens containing oxybenzone and octinoxate in marine tourism areas is considered urgent because the form of the law is made for human welfare and it is a solution to the absence of laws regarding the protection of coral reefs in Indonesia. Adapt selective and responsible law based on facts and environmental data in accordance with responsive legal theory.